أساليب الدعوة من خلال سورة يوسف عليه السلام : دراسة تحليلية - يوسف، أحمد محمد
The correcting methods of Da'wah and educational concepts among preachers and educators are important in this day and age. The weak impact of Da'wah on muslims and non-muslims is not the result of poor Da'wah and its preachers, but is a result of lack of knowledge on the methods and the appropriate means, and also ignorance of some preachers about the concept of Da'wah. In the story of Joseph (p.b.u.h), a good example is given in the selection of appropriate methods and its application on muslims and non-muslims, providing a number of lessons and values in the educational aspects of Da'wah. This study aims to discover methods of Da'wah and education in Surah Yusuf, and devise important lessons with educational values and moral, and some discussion of educational and psychological issues with reference to the Surah. The researcher used the historical method in tracking the events in the story, and descriptive method in investigating the scripture (Surah Yusuf). Apart from that, the views of commentators and specialists in the field of Da'wah and education were also examined. Finally, analytical method was used in devising methods of Da'wah and education based on Surah Yusuf. The researcher reached some important results on the methods of Da'wah and educational values, and some are related to Da'wah and preachers. Surah Yusuf is very much a fascinating surah and has wonderful stories contained in the Qur'an. Although every surah in the Qur'an has its special character, atmosphere and taste, Surah Yusuf and its stories are interesting, not only in one area, but in many ways to make it a unique one.